Buschmann, Rainer F.; Slack, Edward R., Jr. y James B. Tueller. Navigating the Spanish Lake: the Pacific in the Iberian World, 1521-1898. Honolulu: University of Hawaii Press, 2014, xii + 182 pp., ilust. - Bayona, Jorge (2016)
No presenta resumen